Complete Version - Oladokun Omojola, Ph.D, Editor-in-Chief: (Covenant Journal of Communication, 2021)
Â© 2020, Covenant University Journals All rights reserved. No part of this publication may be reproduced, stored in a retrieval system, or transmitted in any form or by any means, electronic, electrostatic, magnetic tape, mechanical, photocopying, recording, or otherwise, without the prior written permission of the publisher. It is a condition of publication in this journal that manuscripts have not been published or submitted for publication and will not be submitted or published elsewhere. Upon the acceptance of articles to be published in this journal, the author(s) are required to transfer the copyright of the article to the publisher.